PENGGUNAAN MEDIA PERMAINAN CONGKLAK DALAM PENINGKATAN HASIL BELAJAR MATEMATIKA - Hasanah, Laela Nur; Aziz, Noor; Mulyani, Pamungkas Stiya (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2024)
Mathematics education plays an irreplaceable role in shaping students' critical, analytical and problem-solving thinking. For students at the elementary level, understanding mathematical concepts in depth provides an important foundation for their future academic abilities and daily life skill. This research aims to investigate the influence of using congklak game media in improving mathematics learning outcomes, specifically on the material of Least Common Multiple (LCM) and Greatest Common Divisor (GCD) for fourth-grade students at MI Ma'arif Kliwonan Wonosobo in the academic year 2023/2024. The research method used was an experiment with a pre-test and post-test control group design. The research sample consisted of two fourth-grade classes, where one class served as the experimental group receiving learning using congklak game media, while the other class served as the control group receiving conventional learning. Data were collected through pre- and post-treatment learning outcome tests. The results of data analysis indicate that the use of congklak game media significantly improves students' mathematics learning outcomes in LCM and GCD compared to conventional learning.